Developing interprofessional education online: An ecological systems theory analysis. Issue 4 (4th July 2017) - Bluteau, Patricia; Clouder, Lynn; Cureton, Debra
ABSTRACT: This article relates the findings of a discourse analysis of an online asynchronous interprofessional learning initiative involving two UK universities. The impact of the initiative is traced over three intensive periods of online interaction, each of several-weeks duration occurring over a three-year period, through an analysis of a random sample of discussion forum threads. The corpus of rich data drawn from the forums is interpreted using ecological systems theory, which highlights the complexity of interaction of individual, social and cultural elements. Ecological systems theory adopts a life course approach to understand how development occurs through processes of progressively more complex reciprocal interaction between people and their environment. This lens provides a novel approach for analysis and interpretation of findings with respect to the impact of pre-registration interprofessional education and the interaction between the individual and their social and cultural contexts as they progress through 3/4 years of their programmes. Development is mapped over time (the chronosystem) to highlight the complexity of interaction across microsystems (individual), mesosystems (curriculum and institutional/care settings), exosystems (community/wider local context), and macrosystems (national context and culture). This article illustrates the intricacies of students' interprofessional development over time and the interactive effects of social ecological components in terms of professional knowledge and understanding, wider appreciation of health and social care culture and identity work. The implications for contemporary pre-registration interprofessional education and the usefulness and applicability of ecological systems theory for future research and development are considered.